2012
DOI: 10.1103/physreve.86.016110
|View full text |Cite
|
Sign up to set email alerts
|

Solid-on-solid single-block dynamics under mechanical vibration

Abstract: The suppression of friction between sliding objects, modulated or enhanced by mechanical vibrations, is well established. However, the precise conditions of occurrence of these phenomena are not well understood. Here we address these questions focusing on a simple spring-block model, which is relevant to investigate friction both at the atomistic as well as the macroscopic scale. This allows us to investigate the influence on friction of the properties of the external drive, of the geometry of the surfaces ove… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 33 publications
2
20
0
Order By: Relevance
“…Discussion -Numerical models for solid friction under vertical vibrations predicted a transition between stickslip and continuous sliding motion governed by the vibration acceleration, with a threshold at Aω 2 g, the gravitational acceleration [19]. The above results demonstrate that, as previously shown in granular assemblies, the vibration velocity, and not acceleration, is the parameter controlling the transition.…”
supporting
confidence: 71%
“…Discussion -Numerical models for solid friction under vertical vibrations predicted a transition between stickslip and continuous sliding motion governed by the vibration acceleration, with a threshold at Aω 2 g, the gravitational acceleration [19]. The above results demonstrate that, as previously shown in granular assemblies, the vibration velocity, and not acceleration, is the parameter controlling the transition.…”
supporting
confidence: 71%
“…Other approaches to friction control include e.g. applying mechanical oscillations [10,11]. While the effect of wettability on lubricated friction has been studied experimentally in macroscopic [12][13][14][15] and nanoscale [16] systems, and modeled using phenomenological finite-element models [17] and simplified molecular dynamics (MD) simulations of nanopatterned surfaces [18,19], less is known about the underlying atomic scale processes and mechanisms responsible for the presence or absence of stick-slip.Given the large surface-to-volume ratio in boundary lubrication, nature of the interaction between the lubricant and the confining surfaces originating from their atomic composition should play a crucial role.…”
mentioning
confidence: 99%
“…Consistently, numerical investigations have also demonstrated that vibrations can advance the time of slip instability [16,17]. Other studies have identified a frequency regime leading to friction reduction [18,19] caused the detachment of the particles from the vibrating confining planes and not related to the fluidization of the granular bed.Here we validate the AF scenario through the numerical investigation of a model system. First we show that perturbations at a characteristic resonant frequency are able to activate acoustic modes inside the fault, promoting the entire system fluidization.…”
mentioning
confidence: 76%
“…Consistently, numerical investigations have also demonstrated that vibrations can advance the time of slip instability [16,17]. Other studies have identified a frequency regime leading to friction reduction [18,19] caused the detachment of the particles from the vibrating confining planes and not related to the fluidization of the granular bed.…”
mentioning
confidence: 76%